A Dendritic Golgi Satellite between ERGIC and Retromer - Mikhaylova, Marina; Bera, Sujoy; Kobler, Oliver; Frischknecht, Renato; Kreutz, Michael R. (Cell Reports, 2016)
The local synthesis of transmembrane proteins underlies functional specialization of dendritic microdomains in neuronal plasticity. It is unclear whether these proteins have access to the complete machinery of the secretory pathway following local synthesis. In this study, we describe a probe called pGolt that allows visualization of Golgi-related organelles for live imaging in neurons. We show that pGolt labels a widespread microsecretory Golgi satellite (GS) system that is, in contrast to Golgi outposts, present throughout basal and apical dendrites of all pyramidal neurons. The GS system contains glycosylation machinery and is localized between ERGIC and retromer. Synaptic activity restrains lateral movement of ERGIC, GS, and retromer close to one another, allowing confined processing of secretory cargo. Several synaptic transmembrane proteins pass through and recycle back to the GS system. Thus, the presence of an ER-ERGIC-GS-retromer microsecretory system in all neuronal dendrites enables autonomous local control of transmembrane protein synthesis and processing. It is unclear whether post-endoplasmatic reticulum carriers in dendrites require a Golgi-related compartment for glycosylation or whether they bypass the Golgi. Mikhaylova et al. find a widespread ER-ERGIC-Golgi satellite-retromer microsecretory system in all dendrites of pyramidal neurons through which a spectrum of synaptic transmembrane proteins might pass and even recycle.
CRIS-Team Scopus Importer:2022-08-05